2019
DOI: 10.1042/bsr20190596
|View full text |Cite
|
Sign up to set email alerts
|

Accurately cleavable goat β-lactoglobulin signal peptide efficiently guided translation of a recombinant human plasminogen activator in transgenic rabbit mammary gland

Abstract: Poor expression is the key factor hampering the large-scale application of transgenic animal mammary gland bioreactors. A very different approach would be to evaluate the secretion of recombinant proteins into milk in response to a cleavable signal peptide of highly secreted lactoproteins. We previously reported rabbits harboring mammary gland-specific expression vector containing a fusion cDNA (goat β-lactoglobulin (BLG) signal peptide and recombinant human plasminogen activator (rhPA) coding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…Moreover, the strong thrombolytic activity of rhPA expressed in their whey was demonstrated by thrombolytic activity assay in vitro. The result demonstrated that the introduction of gGH gene can greatly promote the expression level of rhPA gene in the mammary gland of transgenic rabbits, and the expression level and thrombolytic activity in our study was significantly better [13][14][15][16][17][26][27] .…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Moreover, the strong thrombolytic activity of rhPA expressed in their whey was demonstrated by thrombolytic activity assay in vitro. The result demonstrated that the introduction of gGH gene can greatly promote the expression level of rhPA gene in the mammary gland of transgenic rabbits, and the expression level and thrombolytic activity in our study was significantly better [13][14][15][16][17][26][27] .…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, it is highly possible to improve the expression level of exogenous genes in transgenic animal mammary gland by using GH gene introduction. However, the current strategy to improve the expression level of tPA and rhPA genes in the mammary gland of transgenic animals is often to optimize the gene vector construction [15][16][26][27] . There are few reports on the synergistic promotion of tPA gene expression by double transgenic animals, especially the study of GH gene synergistically promoting the expression of tPA in transgenic animals at home and abroad.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We made a full size replacement of the Csn1s1 ORF from start to stop codon and, as a consequence, the N-terminal Csn1s1 signal peptide (1–15 aa) was replaced with the N-terminal hGMCSF secretion signal (1–17 aa). It is known that native signal peptide could not compete in efficiency with the milk-specific secretion signals, such as BLG N-terminal fragment (1–18 aa) which could improve recombinant protein production by several orders 30 . We have tried to generate hGMCSF transgenic mouse line with preserved Csn1s1 signal peptide through pronuclear microinjection, using the same CRIPSR/Cas9 approach (donor vector + gRNA + Cas9) we conducted in ES cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is frequently employed to create "enriched" milk with improved composition (An et al, 2012;Wan et al, 2012;Yuan et al, 2014), or to achieve large scale production of recombinant human proteins in mouse models (Wu et al, 2012;Burkov et al, 2013;Qian et al, 2014) and in livestock species (Kalds et al, 2019). Milk-specific signal peptides are used in biotechnology to enhance recombinant protein secretion during lactation (Yu et al, 2006;Liu et al, 2014;Lu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%